Comparative Study of Qur'an Learning Management in Indonesia and Thailand - Zulfiatul Khoiroh; Ahmad Rosidi (AFKARINA: Jurnal Pendidikan Agama Islam, 2026)
The Qur'an is the main pillar in Islamic education, both in Indonesia and other Islamic countries such as Thailand. The rapid advancement of technology has given rise to various social challenges, such as declining literacy in reading the Qur'an. This study aims to analyze in depth how Al-Qur'an learning management is applied in MTs. Unggulan Al-Qodiri I Jember, East Java Province, Indonesia, and Samakke Islam Wittaya School, Satun Province, Thailand, with different social backgrounds of students, as well as identify the best Qur'an learning management that other educational institutions can apply. This study uses a qualitative, comparative approach to systematically examine the management of Qur'an learning in schools. Data collection was carried out through observation, documentation, and interviews. As for the results, both schools have a systematic approach to Qur'an learning through the stages of planning, organizing, implementing, and evaluating. MTs. Unggulan Al-Qodiri I Jember excels in the Al-Qur'an education management system through teacher development, the use of external evaluations as a graduation requirement, and the presence of teachers with JUZ. In contrast, Samakke Islam Wittaya School excels in learning intensity and in developing students' talents. This research also formulated a synthesis model of Qur'anic learning management. By bringing together the managerial powers of two institutions, this model establishes a new standard for planning, organizing, implementing, and evaluating Qur'anic learning that is more effective and adaptable.